An Analysis of Reading Comprehension Questions in the Final English Test Given by English Teachers Based on Barret’s Taxonomy at SMAN in Kota Padang - Selvina Salsabila; Yetti Zainil (Universitas Negeri Padang, 2023)
This research aims to analyse the reading comprehension questions given by English Teachers at SMAN Kota Padang based on Barrett’s Taxonomy. This taxonomy has five levels, namely: Literal Comprehension, reorganization, Inferential Comprehension, Evaluation, and Appreciation. This study is being done using a descriptive qualitative research design. To gather the necessary data and information, the observation checklist and interview questions are used as instrumentation. The stages of Barrett's taxonomy were used to categorize the questions that were analysed. The results of this studyindicate that from all the reading questions gathered and observed at six schools and three grades, Inferential Comprehension level has the most questions with 40,07% of the total reading comprehension found in grade X, XI, and XII. It is followed by reorganization level at 35,91%, literal comprehension level at 23,01%, evaluation level at 0,39%, and appreciation level at 0,19%. While the conclusive English assessment at SMAN Kota Padang encompasses all facets of Barrett's taxonomy, its implementation is not necessarily reflected in the formulation of reading inquiries. This discrepancy arises from the dissimilarity between the question distribution across taxonomy stages and the advised proportional distribution. Correspondingly, insights gathered from discussions with the teachers indicated that Barrett's taxonomy had not been integrated into the question development process for the final English test. This affirmation further reinforces the notion that the reading comprehension questions given by English teachers have remained detached from the application of Barrett's taxonomy.